The system of diagnostics of bankruptcy threat to the enterprises - Bivainis, Juozas; Garškaitė, Kristina (Business: Theory and Practice, 2010)
The prepared system of diagnostics of bankruptcy threat to the enterprises, is  presented in the article.  Herein, bankruptcy, threatening the enterprises, is being diagnosed as per three stages, i.e. the condition of the enterprise and the reasons, which have determined such condition, are being gradually concretized. The financial condition of the enterprises and the threat of bankruptcy are being evaluated at the first stage by applying the integrated model, which assists in achieving the generalized evaluation of the condition. The relative financial indices of the enterprise are being analysed at the second stage, seeking for diagnosing the problematic fields of the enterprise. The third stage, at which the absolute financial indices are being analysed, is aimed at ascertaining the reasons, which have determined the condition of the enterprise. The size of the crisis, the crisis factors of activity are ascertained by taking into consideration the evaluation indices of the condition of the enterprise; they allow selecting substantially the bankruptcy prevention measures out of the possible leading set of internal and external measures. The possibilities of adaptation of the prepared system of diagnostics to the enterprises, which are attributed to various economic sectors and to the changing environmental conditions, are foreseen.Article in Lithuanian. Įmonių bankroto grėsmės diagnostikos sistemaSantrauka. Straipsnyje aprašyta parengta įmonių bankroto grėsmės diagnostikos sistema. Pagal ją įmonių bankroto grėsmės diagnostika  atliekama  trimis  etapais,  palaipsniui  konkretinant  įmonės  būklę  ir  ją  sukėlusias  priežastis.  Pirmajame  etape  fi-nansinė  įmonių  būklė  ir  bankroto  grėsmė  vertinama  taikant  integruotą  modelį,  pagal  kurį  gaunamas  apibendrinantis  būklės įvertis. Antrajame etape analizuojami santykiniai finansiniai įmonės rodikliai, siekiant diagnozuoti problemines įmonės sritis. Trečiojo etapo, kuriame analizuojami absoliutiniai finansiniai rodikliai, paskirtis – nustatyti įmonės būklę lėmusias priežastis. Gauti įmonės būklės įverčiai leidžia pagrįstai parinkti bankroto prevencijos priemones iš galimų orientacinio vidinių ir išorinių priemonių  rinkinio.  Numatytos  parengtos  diagnostikos  sistemos  adaptavimo  įvairių  ūkio  sektorių  įmonėms  ir  kintančioms aplinkos sąlygoms galimybės.Reikšminiai žodžiai: įmonių būklės analizė ir vertinimas, bankroto grėsmės diagnostika, integruoto vertinimo modelis, santykiniai finansiniai rodikliai, absoliutiniai finansiniai rodikliai.